STABLE ISOTOPE PROBING TO DOCUMENT BIODEGRADATION UNDER MONITORED NATURAL ATTENUATION CONDITIONS - Kessel, Lowell; Ogles, Dora; Davis, Greg; Key, Katherine; Sublette, Kerry (Águas Subterrâneas, 2011)
não disponivel